2017
DOI: 10.1111/ddi.12594
|View full text |Cite
|
Sign up to set email alerts
|

Ecological uniqueness of stream and lake diatom communities shows different macroecological patterns

Abstract: AimTo discover whether lake and stream diatom communities show different patterns in species richness and in their local (LCBD) and species (SCBD) contributions to beta diversity in relation to macroscale environmental characteristics.LocationFinland.MethodsAs biological data, we used diatom samples collected from Finnish stream (n = 492) and lake (n = 290) sites. As explanatory variable data, we used information on macroscale environmental and historical aspects, such as bedrock, soil and post‐glacial highest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
45
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 86 publications
(60 citation statements)
references
References 41 publications
14
45
0
1
Order By: Relevance
“…water area and wetlands) did not contribute strongly to species richness, we can refute the hypothesis that habitat area per se accounts for variation in species richness at this spatial scale. Although the negative relationship between species richness and LCBD has been noted before in empirical studies of local ecological assemblages (Legendre & De Cáceres, 2013;Heino & Grönroos, 2017;Vilmi et al, 2017;Landeiro et al, 2018), to our knowledge, no study has examined the relationship of LCBD with temperature at large spatial scales across biogeographical provinces. Instead, although we cannot completely rule out the effects of ice age history on the species richness pattern of diving beetles in an area where ice sheet of the Last Glaciation Maximum retreated in a stepwise way between 25 000 and 8000 years before present (Denton & Hughes, 1981;Kleman & Hättestrand, 1999;Houmark-Nielsen et al, 2012), we can nevertheless suggest that climate affects the most variation in species richness across the study area.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…water area and wetlands) did not contribute strongly to species richness, we can refute the hypothesis that habitat area per se accounts for variation in species richness at this spatial scale. Although the negative relationship between species richness and LCBD has been noted before in empirical studies of local ecological assemblages (Legendre & De Cáceres, 2013;Heino & Grönroos, 2017;Vilmi et al, 2017;Landeiro et al, 2018), to our knowledge, no study has examined the relationship of LCBD with temperature at large spatial scales across biogeographical provinces. Instead, although we cannot completely rule out the effects of ice age history on the species richness pattern of diving beetles in an area where ice sheet of the Last Glaciation Maximum retreated in a stepwise way between 25 000 and 8000 years before present (Denton & Hughes, 1981;Kleman & Hättestrand, 1999;Houmark-Nielsen et al, 2012), we can nevertheless suggest that climate affects the most variation in species richness across the study area.…”
Section: Discussionmentioning
confidence: 84%
“…Recently, Legendre and De Cáceres (2013) devised a method to decompose total beta diversity in the contributions of species or sites, where the relative ecological uniqueness of sites can be evaluated [i.e. Empirical research on the topic has thus far revealed that species richness is typically negatively correlated with LCBD across local ecological assemblages, although there is some variation around the relationship (Legendre & De Cáceres, 2013;, Vilmi et al, 2017, Landeiro et al, 2018, da Silva et al, 2018. Empirical research on the topic has thus far revealed that species richness is typically negatively correlated with LCBD across local ecological assemblages, although there is some variation around the relationship (Legendre & De Cáceres, 2013;, Vilmi et al, 2017, Landeiro et al, 2018, da Silva et al, 2018.…”
Section: Introductionmentioning
confidence: 99%
“…Our results seem to be consistent with the idea that the strong physical structuring of the study regions, with the distinct climatic and topographic conditions, override local environmental effects (partially supporting H1). Previous studies have also demonstrated the importance of macroscale descriptors over water chemistry in shaping aquatic community composition (diatoms and macroinvertebrates) in Arctic (Mykrä, Heino, & Muotka, ; Pajunen, Luoto, & Soininen, ; Vilmi, Karjalainen, & Heino, ), temperate (de Mendoza & Catalan, ) and tropical freshwaters (Matthews‐Bird et al., ; Steinitz‐Kannan et al., ).…”
Section: Discussionmentioning
confidence: 95%
“…Shurin, Cottenie, & Hillebrand, ). Earlier studies have shown that lakes and streams partly foster different diatom communities (Kahlert & Gottschalk, ; Soininen & Weckström, ), and that they show differences in species richness and ecological uniqueness patterns (Vilmi, Karjalainen, et al., ). Keeping these earlier observations in mind, it is possible that the differences we now found regarding occupancy and abundance in lakes and streams may be related to levels of connectedness.…”
Section: Discussionmentioning
confidence: 99%
“…To rule out excessive seasonal effects, only samples taken in autumn were considered. A detailed description of the diatom database and data harmonization is presented in Vilmi, Karjalainen, and Heino ().…”
Section: Methodsmentioning
confidence: 99%